Determination of Optimum Speed of a Knitting Machine by Analyzing the Different Parameters - Reza, Mohammad Hosain; Hossain, Kamal (European Scientific Journal, ESJ, 2022)
The objective of this research was to determine the optimum speed of a knitting machine. This study compared the different parameters of a knitting machine running at various speeds. For this, a knitting machine of 22-inch diameter and 24 gauge with 66 feeders knitting 24 Ne yarn was selected and was run at 40 rotations per minute (r.p.m.).; 42 rotations per minute (r.p.m.).; and 44 rotations per minute (r.p.m.) for total 24 hours for each speed. Data was collected for two days for 12 hours each. The different causes of stoppages were recorded with their frequencies and time for total of a 24 hours. Again, actual fabric production and the defective amount were recorded in kg. Moreover, different machine problems (like needle breakage, oil problem etc.) that occurred during the machine running was also recorded. Finally, the efficiency at different speeds was calculated with the help of calculated production and actual production of the knitting machine. Considering the stoppage data, machine efficiency, defective fabric production, and different machine problems, it was found that the optimum speed for the knitting machine is 40 rotations per minute among the three different speeds.